2016
DOI: 10.1177/2150135116661279
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Ring Diagnosis and Management

Abstract: Over 25 years in Southern Nevada, VR prenatal diagnosis has increased, isolated VR age at surgery has decreased, and the percentage of those with RAA-ALS has increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 13 publications
2
34
1
4
Order By: Relevance
“…Our previous 25‐year review showed similar between the years 1990 and 2005 when 66% or 6 of 9 patients operated had a double aortic arch. However, our more current data from our previous report, between the years 2006 and 2015, demonstrated 79% or 34 of 43 patients operated had a RAA‐ALSA VR . In our opinion, the principal reason for this shift is secondary to our high rate of prenatal diagnosis.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Our previous 25‐year review showed similar between the years 1990 and 2005 when 66% or 6 of 9 patients operated had a double aortic arch. However, our more current data from our previous report, between the years 2006 and 2015, demonstrated 79% or 34 of 43 patients operated had a RAA‐ALSA VR . In our opinion, the principal reason for this shift is secondary to our high rate of prenatal diagnosis.…”
Section: Discussionmentioning
confidence: 77%
“…Such factors may include diagnostic methods, populations studied, and inclusion and exclusion criteria. Further, when an RAA with situs solitus is found through an 1 In our opinion, the principal reason for this shift is secondary to our high rate of prenatal diagnosis. In our experience, the fetal echocardiography axial, 3-vessel tracheal view more reliably determines the aortic arch morphology, laterality, and branching pattern than an even an immediate postnatal echocardiogram, and especially more reliably than an echocardiogram performed at an older age.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…At the time of initial cardiac evaluation, a right aortic arch (RAA) is most often first imaged during transthoracic or fetal echocardiography. A right aortic arch is expected in situs inversus with dextrocardia: however, in the presence of situs solitus with levocardia, a RAA is often associated with a vascular ring (VR), an associated surgical intracardiac malformation (AICM), or both . Although our opinion differs, some previous RAA reports have also incorporated double aortic arches .…”
Section: Introductionmentioning
confidence: 82%
“…Along with an improvement in detecting significant congenital heart disease, a secondary effect is an increase in detection of conditions such as RAAs and vascular rings. The fetal echocardiography three‐vessel view is essential to prenatal RAA diagnosis; further, prenatal diagnosis is fundamental to establishing a population's prevalence for conditions, such as a RAA, which, despite the presence of a vascular ring, may be asymptomatic in the newborn and infant period …”
Section: Discussionmentioning
confidence: 99%